ANALISIS POSTFEMINIS PADA NOVEL NAMAKU MATAHARI KARYA REMY SYLADO - Arif Hidayat (Yinyang: Jurnal Studi Islam Gender dan Anak, 2012)
Abstract: This paper reveals novel Namaku Matahari (My Name Is The Sun) by Remy Sylado from the perspective of feminist literary criticism. This novel tells the story of a young woman named Margeretha Geertruida who is trying to find identity through identity as "Sun". The discourse that emerged in the novel is the fault of a woman's interpretation toward her age that her struggle that had been established ends in vain. Therefore, the novel actually emerges the criticism for the errors interpretation of feminism, which deviate from the moral and social existence. Kata Kunci: novel, perempuan, feminis, postfeminis, dan kritik.